2020
DOI: 10.1515/hc-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a new series of thiadiazole derivatives as potential anticancer agents

Abstract: Cancer is one of the most common causes of death in the world. Despite the importance of combating cancer in healthcare systems and research centers, toxicity in normal tissues and the low efficiency of anticancer drugs are major problems in chemotherapy. Nowadays the aim of many medical research projects is to discover new safer and more effective anticancer agents. 1,3,4-Thiadiazole compounds are important fragments in medicinal chemistry because of their wide range of biological activities, including antica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…After these interactions patterns, ADME/T calculations were made to examine how these molecules act in human metabolism. With these calculations, he examines the uptake of molecules into human metabolism, their movements for metabolism, their effects and reactions, and finally their excretion from human metabolism [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…After these interactions patterns, ADME/T calculations were made to examine how these molecules act in human metabolism. With these calculations, he examines the uptake of molecules into human metabolism, their movements for metabolism, their effects and reactions, and finally their excretion from human metabolism [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The anticancer activity of compounds 5a-5f was screened according to the MTT assays. The MTT assays were performed as previously described [19][20][21]. Anticancer activity of nal compounds was assessed against ve different cancer cell lines A549 (lung carcinoma cell line), HeLa (cervical cell line), MCF-7 (human breast adenocarcinoma cell line), HepG2 (human liver carcinoma cell line), and C6 (rat glioma cell line) cell lines as well as NIH3T3 (mouse embryo broblast cell line).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Kaur and Sing [12] published a review on the Thiadiazole analogs as potential pharmacological agents. Thiadiazole derivatives are utilized therapeutically for various diseases thanks to their antiviral [13], anticonvulsant [14] anti-inflammatory [15], anticancer [16] activities. It was also reported that thiadiazole derivatives demonstrated antithyroid activities [17].…”
Section: Introductionmentioning
confidence: 99%